The business model development through co-creation: a case study of Indonesian musician, mocca - Nurwibowo, Muchammad; Dellyana, Dina (The Indonesian Journal of Business Administration, 2018)
Abstract: This study presents the development of business model through co-creation for one of Indonesian musician case, Mocca. The purpose of this study is to solve its business model issue, focusing particularly on co-creation from musician perspective. This paper uses qualitative method and snowball sampling to interview the stakeholders of Mocca with semi structured questions. This paper finds that co-creation has sustained Mocca’s business model as musician, but Mocca needs to develop it in order to sustain and compete with many new players in the music industry. It concludes by identifying how Mocca conduct its co-creation and propose the potential business model and co-creation development strategies to solve its business issues. The proposed co-creation development in this paper includes potential engaging actors, potential value exchange, potential co-creation form, and co-creation flow recommendation.Keywords: business model, business model development, Indonesian musician, co-creation design framework, music industry